Diversion As A Crime Solution Towards Child Crime Prepertrator - Arman Sukma Negara (Faculty of Law, Universitas Lampung, 2021)
Diversion efforts is an alternative solution for the sake of realizing children's interests and protecting the future of children from the destructive effects of imprisonment, which stigmatize criminals in the eyes of the community, but all of these have not been maximally realized because there is a court decision in the Lampung region itself which still applies sanctions punishment as an effective method of providing a deterrent effect on children. Based on this, this research's main problem focuses on implementing diversion for children as a criminal solution for juvenile offenders and whether diversion is an instrument in realizing the best interests of children. This research uses a juridical empirical, and normative juridical approach. The results of the discussion are in this research, namely that in the principle of the best interests of children as a criminal solution for child offenders, diversion is one of the instruments in realizing the best interests of the child considering that diversion instruments for children can improve the child's image from the impression of a criminal. The advice that can be given is that law enforcers should prioritize the principle of the child's best interests in every legal process rather than prioritizing repressive actions that lead to imprisonment sanctions and eliminating children's rights such as protection of their future.